Twitter for Educational Activities in Islamic Higher Education, Why Not? - Rully Agung Yudhiantara (Department of English Language Education, UIN Sunan Ampel Surabaya, 2017)
This research was motivated by the need to combine the trend of using twitter among university students and the need of online educational activities. The study was aimed at investigating: twitter usage between Teacher and students for educational activities.2)discovering students perception on twitter usage for educational activities. This study found that twitter was used for educational activities by teacher and students. The activities occured namely; sharing information,asking and answering, and assigning task. In addition twitter was also used by student to save their document on learning process. Last findings showed that students perceived twitter in a positive manner and they appreciated twitter usage for educational activities.